Teacher’s Perception on Father’s Involvement in Early Childhood Education and Development - Beatriks Novianti Bunga; Maria Leonarda Luruk; Indra Yohanes Kiling (Journal of Health and Behavioral Science, 2020)
Father have important role in young child’s development. Active and regular involvement from father could give positive impacts to child development. In order to understand general description of father’s involvement in Early Childhood Education and Development (ECED) in Kota Kupang, the authors used teacher’s perception as primary data source in this study. The objective of the study is to identify teacher’s perception on fathers’ involvement in ECED in Kupang City. Method used was qualitative with interviews as main data gathering technique. The results showed that father’s involvement in ECED were still limited, proved by statements showing that mother has more active role in ECED compared to father. This is due to the lack of awareness and knowledge of father and other related stakeholders about the importance of father’s involvement in development of their young children. Therefore there are some intervention that need to be applied by teachers in order to improve father’s involvement in ECED that is to give counselling, home visit program, connecting book and also parenting program for fathers.